(untitled) (Journal of University of Babylon for Engineering Sciences, 2020)
Knowledge propositions in the field of architecture have dealt with various propositions and symmetries of various concepts within the field and within many visions, explained this in different directions and the various surroundings conditions. This demonstrated the importance of studying frameworks of a similar relationship between two main concepts in architecture, such as one of them is a recent concept proposed by many studies and research, which is the concept of sustainability with a basic concept that is the theory of the knowledge aspect in architecture, but it is the concept of theory with its knowledge extensions. This paper aims to define the general foundations of both concepts (sustainability and theory), with a detailed explanation and proposition of some of their detailed links within several paths to be a problem of cognitive research (specific knowledge gap about identifying aspects of similarity between indicators of the concepts of sustainability and theory as basic concepts in the field of architecture) and the goal is to clarify and define those Knowledge and then orientation to form the theoretical frameworks that represent their cognitive state. It has fallen into three main vocabulary for both concepts (general position, organizational structure, general indicators) to be compared between the rates of preliminary verification for each of them in that and then applying T You have the frameworks on a specific architectural product that was carefully chosen and then put forward, analyze and discuss the results of this application and explore and clarify the limits of the nature of the relationship of symmetry and the correspondence between the two concepts and their similar indicators so that it becomes clear within the conclusions the strength of the general position and the organizational structure of the two concepts within the general architectural framework versus general and diffuse conceptual theory in its indicators General only.